A wearable pressure sensor based on ultra-violet/ozone microstructured carbon nanotube/polydimethylsiloxane arrays for electronic skins. (5th February 2018) - Yu, Guohui; Hu, Jingdong; Tan, Jianping; Gao, Yang; Lu, Yongfeng; Xuan, Fuzhen
Abstract: Pressure sensors with high performance (e.g., a broad pressure sensing range, high sensitivities, rapid response/relaxation speeds, temperature-stable sensing), as well as a cost-effective and highly efficient fabrication method are highly desired for electronic skins. In this research, a high-performance pressure sensor based on microstructured carbon nanotube/polydimethylsiloxane arrays was fabricated using an ultra-violet/ozone (UV/O3 ) microengineering technique. The UV/O3 microengineering technique is controllable, cost-effective, and highly efficient since it is conducted at room temperature in an ambient environment. The pressure sensor offers a broad pressure sensing range (7 Pa–50 kPa), a sensitivity of ∼ −0.101 ± 0.005 kPa −1 (<1 kPa), a fast response/relaxation speed of ∼10 ms, a small dependence on temperature variation, and a good cycling stability (>5000 cycles), which is attributed to the UV/O3 engineered microstructures that amplify and transfer external applied forces and rapidly store/release the energy during the PDMS deformation. The sensors developed show the capability to detect external forces and monitor human health conditions, promising for the potential applications in electronic skin.